PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE DAN MIND MAPPING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 7 PADANG (Penelitian Eksperimen pada Masa Pendemi COVID-19) - NADYA DERISKA DWI PUTRI (Departemen Matematika, 2020)
Matematical communication skill is an essential component and should be accomplished in mathematics learning. The observation results indicate that the mathematical communication skill of the students in SMPN 7 Padang was still low. Therefore, a research was carried out in order to improve students’ mathematical communication skill by adjusting the Think Talk Write and Mind Mapping (TTW-MM) cooperative learning model. The kind of research was quasy experimental and descriptive with Randomized Control-Group Only Design. Based on the research, it was concluded that the development of mathematical communication skill of students whose during learning process using TTW-MM model has increased, and mathematical communication skill of students whose learning process using TTW-MM model was better than mathematical communication skill of students whose learning with conventional learning. Keywords — Mathematical Communication Skills, Cooperative Learning Model, Think Talk Write, Mind Mapping